2009
DOI: 10.1007/s10126-009-9211-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis

Abstract: Effect of early introduction of microencapsulated diet to larvalAbstract An experimental microdiet prepared using an internal gelation method was used to partially replace the traditional live feed (Artemia) for larval Atlantic halibut, Hippoglossus hippoglossus L. Three trials were conducted with microdiet introduced at 20, 32, and 43 days post first feeding and larvae were sampled at approximately 2, 13, 23, and 33 days after microdiet introduction in each trial. The success of feeding was assessed by morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
0
26
0
3
Order By: Relevance
“…Atlantic halibut larvae using a custom microarray (Douglas et al 2008;Murray et al 2010). The limited number of sequences derived from early embryonic tissues in the microarray platforms used in these studies underscores the importance of having large genome resources to advance our understanding of the molecular mechanisms driving developmental processes in fish larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic halibut larvae using a custom microarray (Douglas et al 2008;Murray et al 2010). The limited number of sequences derived from early embryonic tissues in the microarray platforms used in these studies underscores the importance of having large genome resources to advance our understanding of the molecular mechanisms driving developmental processes in fish larvae.…”
Section: Discussionmentioning
confidence: 99%
“…replacement of fish meal protein by soy proteins), or whether the expression of genes involved in digestion and absorption of macronutrients are altered in the larvae as a result of the introduction of a microencapsulated diet (Murray et al 2009(Murray et al , 2010. The first study showed that Atlantic halibut juveniles tolerate up to 30 % soy protein in the diet, although microarray analysis showed that the expression of several immune markers and genes involved in detoxification increased (Murray et al 2009).…”
Section: Changes In Transcriptome During Larval Development and Nutrimentioning
confidence: 99%
“…The first study showed that Atlantic halibut juveniles tolerate up to 30 % soy protein in the diet, although microarray analysis showed that the expression of several immune markers and genes involved in detoxification increased (Murray et al 2009). Microdiet particles can be readily consumed by halibut larvae after a period of adaptation, providing an adequate source of nutrients with no significant increase in mortality (Murray et al 2010). However, growth of the larvae seems to be impaired and accompanied by an increased incidence of malpigmentation of the eye and the skin, which correlates with changes in the expression of genes involved in pigmentation and eye development (Murray et al 2010).…”
Section: Changes In Transcriptome During Larval Development and Nutrimentioning
confidence: 99%
See 1 more Smart Citation
“…After this time, MS-222 was added to the tanks (Murray et al 2010) and tanks were covered with an opaque board to cease the trial. To adjust light intensity without altering the light spectrum, we used wooden frames that completely covered the top of the experimental tanks and stretched white linen sheets over the frames (Utne-Palm & Stiansen 2002).…”
Section: Light Intensitymentioning
confidence: 99%